Association between hepatitis C infection in Thai patients with oral lichen planus: A case-control study - Trin Manomaivat (2018)
© 2018 John Wiley & Sons Australia, Ltd. AIM: The aim of the present study was to investigate the prevalence of hepatitis C virus (HCV) infection and evaluate liver enzyme levels in patients from upper northern Thailand with oral lichen planus (OLP). METHODS: A case-control study of 101 patients with OLP and 101 patients without OLP was conducted. Peripheral blood was taken from each patient and screened for anti-HCV antibody using immunochromatography. Positive samples were further confirmed using chemiluminescent microparticle immunoassay (CMIA) and reverse transcription-polymerase chain reaction. In addition, liver enzyme levels, alanine transaminase, aspartate transaminase, and alkaline phosphatase were evaluated using spectrophotometry. RESULTS: Immunochromatography and CMIA revealed that nine patients with OLP (8.9%) were positive for anti-HCV antibodies, whereas only one patient without OLP was HCV positive (odds ratio = 9.78). All patients who were HCV positive had significantly higher liver enzyme levels than patients who were HCV negative. CONCLUSIONS: The results of the present study indicated that OLP in certain patients was significantly associated with HCV. This could warrant screening for HCV-infected patients with OLP in Thailand.